Saints and role models in Judaism and Christianity - Schwartz, Joshua.; Poorthuis, Marcel, 1955- (Jewish and Christian Perspectives Series, 2004)
This volume deals with the role of saints and exemplary individuals in Judaism and Christianity. Although sharing the Hebrew Bible and recognizing the same Biblical figures there, both religions have developed widely divergent perspectives upon the significance of these figures, although there are occasional common motifs and themes. Moreover, even the contrasting themes betray an underlying interaction between both religions as is clear from the contributions on, for example, Melchizedek, Elijah, the Desert Fathers, Rabbis on clothing, the Apostle Peter in Jewish tradition, the Maccabees in Christian tradition and the Biblical examples in Saint Antony the Hermit. The book examines Jewish and Christian perspectives upon saints and role models from the Biblical period to the present time. It will be of special importance to scholars and general readers interested in an interdisciplinary approach to theology, rabbinics, history, art history and much more.